EKSPERIMENTASI MODEL PEMBELAJARAN KOOPERATIF TIPE TGT DAN TAI PADA MATERI VEKTOR KELAS XII SMA DITINJAU DARI KREATIVITAS SISWA - Tri Silaningsih; Mardiyana Mardiyana; Riyadi Riyadi (Jurnal Pembelajaran Matematika, 2014)
Abstract: This study aimed to determine: (1) which model produces better learning achievement TGT, TAI, or direct learning model, (2) to find out which one has the better learning achievement between students with high creativity, moderate or low creativity, (3) to determine which one gives better learning achievement between cooperative learning model TGT, TAI or Direct for each student creativity, (4) to find out which one gives the better learning achievement among students who have high creativity, moderate creativity or lower creativity in each of the learning model.This study was a quasi-experimental study with a 3 x 3 factorial design. The sampling technique was done by stratified cluster random sampling. The instrument used for data collection was a questionnaire and math achievement tests. The instrument has been tested by some experts before it is used to conduct trials. Hypothesis testing used two- way Anava with unbalanced cells. Before the Anava test, research data are tested first by test analysis requirements that were test for normality and homogeneity test. The results of two- way Anava analysis show: (1) learning model of TGT and TAI produce better learning achievement, compared to the direct instructional model, while the learning model of TAI and TGT has no difference; (2) Students who have high creativity and moderate creativity have a better learning achievement than the students who have low creativity, the students who have high creativity have better learning achievement than the students who have moderate creativity; (3) students who have creativity of high, moderate or low have on the model TGT learning and TAI have better learning achievement compared to the direct instructional model, while the learning model TGT produce the same learning achievement as TAI learning model; (4) cooperative learning model TGT, TAI and Direct give better result for students who have high and moderate creativity than students who have low creativity, as well as the students who have high creativity provide a better learning achievement than moderate creativity.Keywords: Learning TGT, TAI, and creativity